1998
DOI: 10.2307/2463361
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Coevolution over Productivity Gradients

Abstract: This study addresses the question of how spatial heterogeneity in prey productivity and migration act to determine geographic patterns in antagonistic coevolution with a predator. We develop and analyze a quantitative coevolutionary model for a predator-prey interaction. If the model is modified appropriately, the results could broadly apply to multispecies communities and to herbivore-plant, parasite-host, and parasitoid-host associations. Model populations are distributed over a gradient in prey birth rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
141
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(155 citation statements)
references
References 0 publications
12
141
1
1
Order By: Relevance
“…More tests on the shape of the trade-off of being defensive and growth of the bacterial prey will be required as well as on the counter-defence mechanism of the ciliates (potential mechanisms are behavioural, morphological or physiological adaptations). In addition to effects of predator evolution on prey adaptation examined in here, previous studies have identified resource availability and temporal and spatial differences as important drivers for the co-evolutionary dynamics in host-parasite systems 35,36,49 as well as for prey evolution in predator-prey systems 29,33 . In our study, resources, that is, productivity was constant across treatments, but differences in traits of the predators had similar effects as differences in production: co-evolved predator populations increased rapidly at the beginning of the experiment resulting in high predator-prey ratios and higher encounter rates.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…More tests on the shape of the trade-off of being defensive and growth of the bacterial prey will be required as well as on the counter-defence mechanism of the ciliates (potential mechanisms are behavioural, morphological or physiological adaptations). In addition to effects of predator evolution on prey adaptation examined in here, previous studies have identified resource availability and temporal and spatial differences as important drivers for the co-evolutionary dynamics in host-parasite systems 35,36,49 as well as for prey evolution in predator-prey systems 29,33 . In our study, resources, that is, productivity was constant across treatments, but differences in traits of the predators had similar effects as differences in production: co-evolved predator populations increased rapidly at the beginning of the experiment resulting in high predator-prey ratios and higher encounter rates.…”
Section: Discussionmentioning
confidence: 90%
“…In some cases this evolutionary change has also been documented to directly affect the ecological dynamics 10,16,17,[32][33][34] . In addition to the strong evidence that the prey or host populations can evolve adaptations, there are observations that exploiter species (predators or parasites) can evolve within ecologically relevant time scales 33,35,36 . Furthermore there is evidence that both the consumer and the resource species evolve; a defensive adaptation in the prey (host) is followed by counter adaptation in the predator (parasite), which then causes further adaptation in the prey and so on, leading to antagonistic co-evolutionary dynamics 37 .…”
mentioning
confidence: 99%
“…High-quality habitats may have different evolutionary optima for defence strategies by hosts and offensive strategies by parasites (Hochberg & van Baalen, 1998). Evolution towards different optima under different environmental conditions may render interpretation of experimental studies difficult.…”
Section: Environmental Heterogeneity: Yet Another Level Of Complicationmentioning
confidence: 99%
“…Depending on its rate, gene flow can facilitate local adaptation by supplying new genetic variation or inhibit adaptation by swamping existing variation with less fit alleles (25). The relative matching between prey behavior and predator selection could play an important role in structuring species interactions and emergent community properties (26,27).…”
mentioning
confidence: 99%